Constructing built-in electric field in graphitic carbon nitride hollow nanospheres by co-doping and modified in-situ Ni2P for broad spectrum photocatalytic activity. (10th November 2021) - Zhang, Linlin; Peng, Wenxing; Li, YaKun; Qin, Rui; Yue, Dong; Ge, Chengjun; Liao, Jianjun
Abstract : S and O co-doped g-C3 N4 hollow-nanospheres modified in-situ by Ni2 P is obtained. Ni2 P/SOHC3 N4 acts as an effective photocatalyst for stable photocatalytic property. Ni2 P traps the electrons from co-doped g-C3 N4 for boosting charge separation. Hollow structure for g-C3 N4 generates more active sites for photocatalytic reaction. Abstract: The construction of built-in electric field is generally considered as an effective strategy to enhance photocatalytic performance due to its significant role in charge separation. Herein, a built-in electric field within g-C3 N4 hollow nanospheres co-doped with sulfur and oxygen and modified in-situ Ni2 P is proposed. Ni2 P/SOHC3 N4 exhibits significantly enhanced board spectrum photocatalytic properties for hydrogen precipitation (5.21 mmol h −1 g −1 ) and photocatalytic Cr(VI) reduction without the use of noble metal. It also achieves high photocatalytic sterilization activity and remarkable stability when used to completely inactivate E. coli (10 7 ) in 60 min under Vis-NIR light irradiation. The enhanced performance is attributed to the formation of a curved hollow sphere structure, which promotes the electron transfer between the inner and outer layers. In addition, co-doping inhibits the recombination of photogenerated carriers, and the built-in electric field recombined with Ni2 P facilitates the electron transfer between the composite interfaces. This design strategy demonstrates an original method of devising multifunctional photocatalysts with enhanced activity and stability. Graphical abstract: Image, graphical abstract